Spatial effects of willingness-to-pay: The case of two nuclear risks - Peter Zweifel; Yves Schneider; Christian Wyss (University of Zurich, Socioeconomic Institute, 2007)
This paper examines the spatial dimension of marginal willingness to pay (MWP) for reduction of nuclear risks through increased insurance coverage. The effect of distance from a nuclear power plant on individuals' MWP is ambiguous. MWP is expected to decrease with distance because the risk of being affected by an accident decreases. However, if individuals choose their residential location taking the operational risk into account, MWP is predicted to first increase and later decrease with distance from the nuclear power plant. On the other hand, there are risks associated with transportation and disposal of nuclear waste where distance should matter only in the vicinity of the plant. These theoretical predictions are tested with data collected using a stated choice experiment. The predictions are largely confirmed by the evidence.
Keywords: C25; K13; L94; 330; discrete-choice experiment; liability insurance; nuclear accident; willingness to pay; Kernkraftwerk; Nukleare Entsorgung; Externer Effekt; Willingness to pay; Schweiz